Joining Panel Data with Cross-Sections for Efficiency Gains: an Application to a Consumption Equation for Nicaragua - Randolph Bruno; Marco Stampini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
This paper explores how cross-sectional data can be exploited jointly with longitudinal data, in order to increase estimation effciency while properly tackling the potential bias due to unobserved individual characteristics. We propose an innovative procedure and we show its implementation by analysing the determinants of consumption in Nicaragua, based on data from three Living Standard Measurement Study surveys from 1993, 1998 and 2001. The last two rounds constitute an unbalanced longitudinal data set, while the first is a cross-section of di®erent households. Under the assumption that the relationship between observed and unobserved characteristics is homogenous across time, information from longitudinal is are used to clean the bias in the unpaired sample. In a second step, corrected unpaired observations are used jointly with panel data. This reduces the standard errors of the estimation coe±cients and might increase their significance as well, otherwise compromised by the limited variation provided by the short longitudinal data.
Keywords: 330